Some observations on the three variants of the Shuar numerical system - Valeš, Miroslav (Romanica Olomucensia, 2016)
The limited ability of the Shuar language to express number drew the attention of the first researchers who came into contact with this ethnic group in the Ecuadorian Amazon. The aim of this paper is to demonstrate and exemplify the changes by comparing the situation that the early researchers found, Gnerre's observations made in the '70s of the last century, and the current situation. The fundamental data come from the author's own research carried out among the Shuar since 2010. The results reveal the dynamics and vitality of three competing numerical systems. The situation of language contact has led not only to the decline of the original numerical system, but also to the limited use of the new system introduced by the missionaries. Finally, the use of numbers in Spanish is the most common option of all bilingual speakers.
Keywords: Shuar; numeral; vernacular numerical system; vitality; bilingual education.